Lighting Enhancement of Classrooms in Heritage School Buildings Based on the Greenship Rating Tools: Lighting Enhancement of Classrooms Based on the Greenship Rating Tools - Susan, Susan; Prihatmanti, Rani (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
This study aims to suggest some strategies for improving the quality of lighting in adaptive reuse buildings. Recently, several concerns have been raised about the lighting environment of heritage buildings that have been adaptively reused for a different function. These changes may lead to a problem for the occupants of the building, particularly on the indoor lighting quality. It is regarded as one of the most affected variables in the building of heritage that is adaptively reused. Green Building Council Indonesia (GBCI) has been concerned about this issue, particularly to the requirements related to lighting power density and control, visual comfort, outside view, and daylight. The purpose of this research is therefore to suggest some strategies for improving the quality of lighting in the two classrooms of two heritage schools in Surabaya, Indonesia, based on the Greenship Interior Space rating tool. There are three credits for lighting power density and control, and one credit for visual comfort criteria. By performing light mapping measurements, calculations, and computer simulation, this analysis is qualitative. To capture the condition of the classrooms examined, building observation was also performed. The observation shows that the existing condition gains four credits only. If adopted, the strategies proposed could achieve eight credits, which is covers 80% of the assessment points. The higher credits achieved reflect a better lighting environment and better value for energy efficiency and conservation.